Socket Preservation with Hydroxyapatite Gipsum Puger Scaffold and Aloe vera on Fibroblast and Type 1 Collagen Cells - Amiyatun Naini; Clarissa Astiasari; Muhammad Nurul Amin (Denta Journal Kedokteran Gigi, 2022)
Background: The prevalence of tooth extraction was 7.29% according to RISKESDAS 2018. Post-tooth extraction will cause injury and bone resorption. Scaffold material combination of hydroxyapatite gypsum puger (HAGP) and aloe vera (AV) can be used for preservation of extraction socket. Objective: To analyze fibroblast and type 1 collagen cells in the extraction socket after being induction by a combination of hydroxyapatite gypsum puger scaffold and aloe vera. Materials and Methods: Making a combination of gypsum puger hydroxyapatite scaffold and aloe vera, divided into four groups, namely negative control, aloe vera scaffold, HAGP scaffold, and HAGP+AV scaffold. Extraction of the mandibular 1st molar in Wistar rats, the application on the extraction socket was waited for 3, 5, 7, and 14 days. Preparation of preparations using Hemaktocillin Eosin staining method. Results: LSD test on the HAGP+AV scaffold group between days 3 and 5, days 3 and 7, days 3 and 14, days 5 and 7, days 5 and 14, days 7, and 14 were obtained (p=0.000), this shows a significant difference between the treatment groups. The results of type 1 collagen in the HAGP+AV scaffold group between days 3 and 14 were obtained (p=0.005) showing a significant difference. Each group on day 14 showed the highest number of fibroblast and type 1 collagen cells. Conclusion: The combination of HAGP+AV+gelatin scaffold can increase fibroblast cells and type 1 collagen after tooth extraction. The socket healing process is getting faster on day 14.